Factors associated with paediatric medulloblastoma- a descriptive study of patients with medulloblastoma treated in Johannesburg (2015-2022) - Mazibuko, Lucas Thapelo (University of the Witwatersrand, Johannesburg, 2025)
Background: Medulloblastoma is the most common malignant neoplasm of the central nervous system in children. This pathology originates from the cerebellum and predominantly impacts children aged 3 to 8 years. Notwithstanding the progress made in therapeutic approaches, medulloblastoma persists as a considerable contributor to both morbidity and mortality in children. Objectives: This study aimed to describe the epidemiology, clinical presentation, stage, histopathology, treatment, complications and outcome of medulloblastoma in children who were treated at Chris Hani Baragwanath Academic Hospital (CHBAH) and Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) from 2015 to 2022. Method: This retrospective cohort study examines all patients diagnosed with medulloblastoma from January 2015 to December 2022. The data utilised in this analysis were gathered from clinical and radiological records and histopathology reports from the National Health Laboratory Services (NHLS). Results: A total of twenty-seven patients were diagnosed with medulloblastoma; however, only twenty patients met the study's inclusion criteria. Two patient files were missing, and five contained incomplete information. The cohort consisted of more girls than boys, with a ratio of 1.2:1. Ninety-five per cent of the children were Black, while 5% were of Indian descent. Symptoms were present for an average of four weeks before presentation. The most common presenting signs and symptoms were gait abnormalities (80%), headaches (60%), and nausea and vomiting (60%). Histopathological analysis revealed that 55% of cases were unspecified medulloblastoma, 35% were desmoplastic/nodular, and 10% were classified as classic medulloblastoma. All the patients in our cohort had debulking surgery. Sixty-five per cent of patients completed both chemotherapy and radiotherapy; 20% were referred to palliative care post-surgery, and 15% succumbed to complications such as pneumonia, surgical-site infections, and recurrent urinary tract infections. Among those who died, two of the three patients were three years old or younger, all showing advanced stages of the disease upon presentation. iii Conclusion: In the cohort of patients who died, all had presented with advanced disease and residual tumours larger than 1.5 cm². This study highlights that several factors, including the size of post-operative residual tumours, the timing of diagnosis, and the completion of treatment, influence the outcomes for medulloblastoma. Early detection, complete surgical resection, and the successful execution of adjuvant therapy are vital components in enhancing patient survival rates. There is a need for future prospective studies with larger sample sizes to deepen our understanding of prognostic factors and to optimise treatment strategies in this context.
A research report submitted in fulfillment of the requirements for the Master of Medicine, in the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2025
Keywords: Medulloblastoma; Paediatric; UCTD; SDG-3: Good health and well-being